The Relationship Between Mild Cognitive Impairment and Daily Living Activities in the Elderly at the Dewi Sartika Cokrobedog Community Health Post - Ikbal Hasan Fauzi; Siti Nadhir Ollin Norlinta; Muhammad Irfan (International Journal Of Health Science, 2026)
The increasing number of older adults and longer life expectancy have led to various health challenges, including cognitive decline. Mild Cognitive Impairment (MCI) is a condition that occurs in the transitional stage between normal aging and dementia. It is characterized by decreased memory, attention, language, visuospatial ability, and executive function, although it does not yet significantly disrupt basic daily activities. However, this condition can influence the independence of older adults in performing Activities of Daily Living (ADL), particularly instrumental activities that require higher cognitive abilities such as managing finances, shopping, preparing meals, and using transportation. If cognitive decline is not properly managed, it may increase dependency, raise the risk of injury, and reduce the quality of life of older adults. This study aimed to analyze the relationship between Mild Cognitive Impairment and Activities of Daily Living among older adults at Posyandu Dewi Sartika Cokrobedog. The research applied a quantitative cross-sectional design with a sample of 93 older adults selected using purposive sampling. Cognitive function was assessed using the Montreal Cognitive Assessment Indonesian version (MoCA-Ina), while daily functional ability was measured using the Lawton Instrumental Activities of Daily Living (IADL) scale. Data were analyzed using the Shapiro–Wilk normality test and Spearman Rank correlation. The results showed a significant relationship between Mild Cognitive Impairment and ADL independence (p < 0.05) with a moderate correlation, indicating that better cognitive function is associated with greater independence in daily activities.